Association of body composition with clinical outcome in Chinese women diagnosed with breast cancer - Liu, Xinyi; Zhang, Enming; Wang, Suxing; Shen, Yixiao; Xi, Kaiwen; Fang, Qiong (Frontiers in Oncology, 2022)
Objective: To explore the association of body composition with clinical outcomes in Chinese women diagnosed with breast cancer. Method: A total of 2948 Chinese female patients with breast cancer have been included in this retrospective study. Body composition mainly includes the measurements of adiposity and muscle mass. Visceral fat area (VFA) is used to measure visceral obesity, while appendicular skeletal muscle mass index (ASMI) is utilized to evaluate sarcopenia. The endpoints of this study are disease-free survival (DFS) and overall survival (OS). The association of the body composition parameters with DFS and OS was statistically analyzed. Result: The median follow-up time for survivors was 42 months (range, 3 to 70 months). 194 patients (6.6%) had breast cancer recurrence and 32 patients passed away (1.1%). Among the 2948 included patients, 1226 (41.6%) patients were viscerally obese, and 511 (17.3%) patients were sarcopenic. We found that visceral obesity had a significant prognostic impact on DFS (HR 1.46; 95% CI 1.10-1.95; p = 0.010) but not on OS (P = 0.173). Multivariate analysis revealed sarcopenia as independent prognostic factors for DFS (HR 1.44; 95% CI 1.02-2.03; p = 0.038) and OS (HR 2.13; 95% CI 1.00-4.51; p = 0.049). BMI was not significantly associated with both DFS (P = 0.224) and OS (P = 0.544). Conclusion: Visceral obesity is associated with a higher risk of disease recurrence, and sarcopenia is significantly associated with increased recurrence and overall mortality among Chinese women with breast cancer. Body composition assessment could be a simple and useful approach in breast cancer management. Further study can focus on decreasing visceral fat and increasing skeletal muscle mass to improve prognosis in breast cancer survivors.